Attributive function of the instrumental case with the semantics of the method of action in the dialects of the Carpathian region - Юсікова, Олена Віталіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The article clarifies the structural and semantic features of the attributive in the form of the instrumental case with the semantics of the mode of action in the dialects of Transcarpathia. The functional essence of the attributive is considered, which are called the signs of individual actions, situations of objective reality. Highlighted the functional essence of the attributive instrumental case in the position of the adverb. The purpose of this article is to highlight the formal-syntactic features and semantic manifestations of the peripheral zone of attributiveness, namely, the attributes with the semantics of the mode of action in the form of the instrumental case. The instrumental attributes in the studied dialects characterize various actions, situations and retain semantic and morphological connections with words, phrases, and sentences. They can be synonymous with nouns in other indirect cases or with verb constructions in the form of subordinate clauses. Their ability to convey variable, temporal and situational signs is associated with a specific subject correlation with the attributives in the form of the instrumental case. Achievement of this goal presupposes the solution of the following specific tasks: 1) to establish the initial semantically elementary sentence that underlies the attributives with the semantics of the mode of action, the lexical meanings of the supporting and dependent components; 2) find out the functional and semantic meaning of the attributive syntaxem. Within the framework of the attributive components in the form of the instrumental case, having the semantics of the mode of action, one can distinguish groups: the names of the methods of production processes, the names of the external characteristics of movement in space, the names of the generalized characteristics of the action, characteristics as a result of an action, the external characteristics of a person or animal; the names of the external characteristics of plants; the names of a qualitative characteristic of an individual action.